(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The methods for obtaining of sodium aluminate, aluminium sulfate, aluminium hydroxide, aluminium hydroxychloride and alumo-ammonium applied products from aluminium-containing industrial wastes have been studied. The goal products synthesized by means of elaborated methods could be used in paper, leather, textile, artificial precious stones industry as well as catalysts for natural and waste waters treatment processes.